PENGARUH INVESTASI TERHADAP PROFITABILITAS ANGGOTA HOLDING PT PUPUK INDONESIA (PERSERO) - Rahmat Setiawan; Koko Sudiro (Sekolah Tinggi Ilmu Ekonomi Semarang, 2019)
In anticipation of future competition,, the Ministry of SOE since 2011 has set an aggressive strategy in holding management on PT Pupuk Indonesia (Persero). PT Pupuk Indonesia holding members are directed to be more expansive in improving their performance both by increasing their working capital and fixed assets. This expansion is expected to be able to increase the company's profitability.This research was conducted using a quantitative approach to assess the effect of working capital investment variables and fixed asset investment on the company's profitability variable. Data is obtained from the quarterly financial statements of the holding member of PT Pupuk Indonesia (Persero) during the period after the establishment of a strategic holding in 2011-2016.The results showed that the investment policy on working capital, as measured by the ratio of Current Assets / Total Assets, had a significant positive effect on ROA and ROE. While the investment policy on fixed assets, as measured by the ratio of Fixed Assets / Total Assets, has a significant negative effect on ROA and ROE